Karakterisasi Kalsium Karbonat (CaCO3) Dari Cangkang Landak Laut (Diadema setosum) - Eko Cahyono; Juanita Fani Jonas; Bella Anjelika Lalenoh; Nurfaida Kota (Universitas Sriwijaya, 2019)
Sea urchin is an aquatic animal that contains calcium carbonate. Calcium carbonate usually extracted from solid limestone suspension but in this case, calcium carbonate is extracted from sea urchin exoskeleton. The aim of this research is to characterize the calcium carbonate preparation from sea urchin exoskeleton. All steps in this research included destruction, extraction, and precipitation. All characteristic of calcium carbonate preparation from sea urchin exoskeleton is water content 12.83±1.33%, ash 37.10±1.02%, fat content 0.93±0.06%, protein content 2.01±0,67% and carbohydrate by-Difference 47.12±4.12. For characterization of calcium carbonate are rendement 64.29±0.60%, water content 0.69±0.30%, ash 57.23±0.25%, calcium content 25.53±2.50%, and FTIR spectroscopic identified OH¯ dan CO3. Absorbent bend of OH group appears in 3420.57 cm-1 and CO3 group in872.89 – 1416.66 cm-1.